Studi Transformasi Digital terhadap Manajemen SDM Global: Systematic Literature Review - Fadilah, Nuriya; Anshori, Mochammad Isa (Innovative: Journal Of Social Science Research, 2025)
This research examines the effect of digital transformation on human resource management (HRM) in global organizations using the Systematic Literature Review (SLR) approach. It focuses on how digitalization, through technologies like HRIS and automation, impacts operational efficiency, employee retention, and various HR functions. Data were gathered from the top 34 journals (2017-2024) in Google Scholar using Publish or Perish (PoP). Results show enhanced productivity, work flexibility, and employees' digital skills, though challenges such as resistance to change and skill shortages were noted. The study advises companies to factor in ethical and social responsibility considerations when adopting technology. Limitations include the sources and timeframe of the data, suggesting future research should expand the scope of sources and duration.